Polymer–peptide hybrids as a highly immunogenic single-dose nanovaccine. (January 2014) - Ahmad Fuaad, Abdullah AH; Jia, Zhongfan; Zaman, Mehfuz; Hartas, Jon; Ziora, Zyta M; Lin, I-Chun; Moyle, Peter M; Batzloff, Michael R; Good, Michael F; Monteiro, Michael J; Skwarczynski, Mariusz; Toth, Istvan
Aim: To explore four-arm star poly(t-butyl)acrylate (P t BA)–peptide and linear P t BA–peptide conjugates as a vaccine-delivery system against Group A Streptococcus.Materials & methods: P t BA nanoparticles bearing J14 peptide epitopes were prepared via alkyne-azide 1, 3-dipolar cycloaddition 'click' reaction. The conjugated products were self-assembled into small or large nanoparticles. These nanoparticle vaccine candidates were evaluated in vivo and J14-specific antibody titers were assessed.Results & discussion: Mice vaccinated with the nanoparticles were able to produce J14-specific IgG antibodies without the use of an external adjuvant after a single immunization. We have demonstrated for the first time that the immune responses against self-assembled P t BA nanoparticles are stronger for the smaller sized (˜20 nm) nanoparticles compared with the larger (˜500nm) P t BA nanoparticles.Conclusion: PtBA analogs have the potential to be developed as potent carrier systems for single-dose synthetic vaccines. Original submitted 29 August 2012; Revised submitted 6 December 2012; Published online 23 April 2013